Effects of amylose content and chemically cross-linking starch on in-vitro digestibility and extrusion of starch - Shukri, Radhiah (Kansas State University, 2013)
This study focused on in-vitro digestibility and pasting properties of cross-linked (CL) starch with different amylose contents and different cross-linking levels, as well as physicochemical properties of extruded wheat flours with different amylose contents and functionality of amylopectin and cross-linking in improving the textural and physical properties of oat flour extrudates. Starch was CL by phosphorylation using a mixture of sodium trimetaphosphate and sodium tripolyphosphate at the ratio of 99:1 under alkaline condition. The digestibility of highly CL maize starches with different amylose contents was determined by Englyst, Available Carbohydrate Dietary Fiber and Association of Official Analytical Chemists (AOAC) Method 991.43 methods. CL waxy and normal maize starch granules swelled much more at higher temperatures, resulting in significantly lower total dietary fiber content than high-amylose maize starch. The alkali treatment study on low levels of cross-linking in starch affected the ratios of total bound phosphate esters which changed the degree of starch swelling, crytallinity and pasting properties of the CL starch. The study on the mechanism of the digestive enzymes and the extent of digestion during the incubation of CL wheat starch in AOAC Method 2009.01 showed progressive digestion after 16 h of incubation, which may not reflect in-vivo response in human. Extrusion of normal and waxy wheat flours resulted in the breakdown of starch and an increase in the insoluble protein, which affected the textural and structural properties of extrudate. High energy input played a major role in radial expansion of normal hard wheat extrudate, whereas higher amylopectin in soft waxy wheat flour was a dominant factor in determining the radial expansion when compared to normal soft wheat. Inclusion of soft waxy wheat in the oat flour formulations at 18% moisture content improved the textural and structural properties of extrudates. Low cross-linking level of CL waxy maize starch in oat flour formulation increased the void fraction and reduced the breaking strength of extrudates, whereas higher cross-linking levels of CL starches improved the resistant starch level on oat flour formulation but had very poor structural and textural properties.The study offers a good insight on the properties and digestibility of CL starch, as well as using low levels of CL starch to improve textural properties of nutritional extruded products. In addition, study on the extrusion of wheat flours with different amylose and protein contents provides knowledge on the influence of chemical compositions and energy input on the physico-chemical properties of extrudates.
Amylose content and chemically cross-linking starch on in-vitro digestibility and extrusion of starch
Keywords: Cross-linked starch; In-vitro digestibility; Extrusion; Agriculture, General (0473); Food Science (0359)